Layer-Specific Vesicular Glutamate Transporter 1 Immunofluorescence Levels Delineate All Layers of the Human Hippocampus Including the Stratum lucidum - Woelfle, Sarah; Boeckers, Tobias M. (Frontiers in Cellular Neuroscience, 2021)
The hippocampal formation consists of the Ammon’s horn (cornu Ammonis with its regions CA1-4), dentate gyrus, subiculum, and the entorhinal cortex. The rough extension of the regions CA1-3 is typically defined based on the density and size of the pyramidal neurons without clear-cut boundaries. Here, we propose the vesicular glutamate transporter VGLUT1 as a molecular marker for the CA3 region. This is based on its strong labeling of the stratum lucidum (SL) in fluorescently stained human hippocampus sections. VGLUT1 puncta of the intense SL band co-localize with synaptoporin (SPO), a protein enriched in mossy fibers (MFs). Owing to its specific intensity profile throughout all hippocampal layers, VGLUT1 could be implemented as a pendant to Nissl-staining in fluorescent approaches with the additional demarcation of the SL. Furthermore, by high-resolution confocal microscopy, we detected VGLUT2 in the human hippocampus, thus reconciling two previous studies. Finally, by VGLUT1/SPO co-staining, we provide evidence for the existence of infrapyramidal MFs in the human hippocampus and we show that SPO expression is not restricted to MF synapses as demonstrated for rodent tissue.